Teaching Children's Multiple Intelligences through the Kitab Ta'lim Fadhilah Amal: A Study on a Jama'ah Tabligh Family Group - Jaafar, Azhar; Langputeh, Sukree; Zemoura, Nawal; Taufan, Muhammad; Kamaruzaman, Nur Rasyidah (Khalifa: Journal of Islamic Education, 2025)
Multiple intelligences are the basic potential granted by Allah SWT to all humans. For children, this intelligence needs to be nurtured, trained, and developed from an early age in a sustainable manner. In the context of Islamic education, there are many ways parents can cultivate a child’s multiple intelligences, for example by reading historical accounts and stories contained in books related to multiple intelligence education. The Kitab Ta’lim Fadhilah Amal is the main reading for the Jama’ah Tabligh da’wah movement group in educating each family member, including their children. In general, this book contains history and messages of life, worship, and spirituality from the Prophet Muhammad SAW, his companions, and previous scholars, presented in the form of stories. This study specifically aims to analyze the effect of story-based education from the Kitab Ta’lim Fadhilah Amal, as practiced by parents, on the development of children’s multiple intelligences in Jama’ah Tabligh families. This research employs a qualitative method with an ethnographic approach. Data were collected through interviews with forty informants selected using a purposive sampling technique. The informants consisted of parents, children, and leaders of Jama’ah Tabligh groups in three different countries: Malaysia, Indonesia, and Thailand. To strengthen the interview data, the author also conducted four years of observation by directly participating in the family activities of the Jama’ah Tabligh group, such as Ijtima’, Bayan Markas, Ta’lim Halaqah, Khuruj, and Jaulah, and even visiting the homes of all informants. All interview and observation data were thematically analyzed using NVivo 12 software. The research findings identified four aspects of intelligence that emerged from story-based education in the Kitab Ta’lim Fadhilah Amal that influenced children’s multiple intelligences. These include: (i) verbal-linguistic intelligence, (ii) intrapersonal intelligence, (iii) interpersonal intelligence, and (iv) spiritual intelligence. The findings of this study can serve as a guide for parents to nurture and develop children’s multiple intelligences from an early age in Muslim families.